The Influence of Fee Based Income on Gross Profit Margin and Profit Margin Ratio of Sharia Commercial Bank in Indonesia Period 2018 to 2023 - Arvika, Arvika; Parno, Parno; Mainata, Dedy (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2024)
The financial reports of Islamic Commercial Banks (BUS) for the years 2018–2023 that are posted on the websites of the Financial Services Authority (OJK) and associated Islamic Commercial Banks (BUS) serve as the primary source of secondary data for this quantitative research type study. Panel data regression with Fixed Effect and Random Effect models is the data analysis technique employed. E-Views 12 is the analysis tool that was utilized. The results of this study partially show that the Fee-based Income variable has no effect on the Gross Profit Margin of Islamic Commercial Banks for the 2018- s.d 2023 period with a t-statistic value <t table (0.384 <1.970) and a probability value of more than 0.05 (0.70 > 0.05). Fee Based Income has no partial effect on the Profit Margin Ratio of Islamic Commercial Banks with a statistical t value < t table (-0.258 < 1.970) and a probability value greater than 0.05 (0.79 > 0.05). So it can be concluded that Fee Based Income has no partial effect on Gross Profit Margin and Profit Margin Ratio of Islamic Commercial Banks.